IMPLEMENTASI MODEL CLAIM, EVIDENCE, REASONING (CER) DALAM PEMBELAJARAN MENULIS TEKS ARGUMENTASI SISWA FASE D MENGGUNAKAN PENDEKATAN STEAM - Darnialis; Priyanto; Lusia Oktri Wini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Abstrak This study aims to describe the implementation of the Claim, Evidence, Reasoning (CER) model in learning argumentative text writing for Phase D students using the STEAM approach at SMP Nurul Khoir Jambi. This research employed a qualitative descriptive method involving 36 students from class IX A and IX B. Data were collected through observation, interviews, and documentation in the form of students’ argumentative writing assignments. The assessment focused on five aspects, namely claim, evidence, reasoning, argumentative text structure, and language use. The results showed that the implementation of the CER model had a positive effect on students’ argumentative writing skills. A total of 14 students achieved the “very good” category, 9 students were categorized as “good,” 1 student was categorized as “fair,” and 12 students were categorized as “poor.” The average score of class IX A was 67.8, while class IX B obtained an average score of 77.6. Students in the very good category were able to develop claims, evidence, and reasoning systematically and logically. The STEAM approach helped students connect learning with real-life issues such as social media, reading habits, gadget use, and school environmental cleanliness. Therefore, the implementation of the CER model using the STEAM approach can improve students’ critical thinking and argumentative writing skills.